Slant Estimation and Correction for Online Handwritten Bengali Words - Mandal, G; Biswas, T (International Journal of Computer Sciences and Engineering, 2025)
Slant is a common artefact inwhich handwritten word takes the form of slope and handwriting recognition system becomes less accurate. For this reason slant estimation and correction is a standard step in handwriting recognition systems for processing written text after skew detection and correction. If Skew correction and Slant correction are done successfully then recognition part will be more prominent. Handwritten characters of natural handwriting are usually italicized due to mechanism of handwriting and personality. In this paper the slant of the Bengali online handwritten words has been estimated and has been corrected. In slant estimation and correction, we have used Projection profile histogram method to detect core region or busy zone of the handwritten words and we defined the estimated head line (matra) and estimated base line of the words. Then we have detected almost vertical (considering a threshold value of angle 45 degree) straight lines which meet or closer to meet the head line (matra) and baseline of the core region present inside the words. After detecting those vertical straight lines we have calculated angle of slant of each vertical straight lines separately and calculated average slant angle. Then rotate all the pixels into the particular slant angle to do slant correction considering the base as fixed point. We have tested this proposed technique on 2655 Bengali handwritten words and have achieved an outstanding result of 96 percentage of accuracy.